Water Supply Systems: Past, Present Challenges, and Future Sustainability Prospects - Andreas N. Angelakis; Andrea G. Capodaglio; Rohitashw Kumar; Mohammad Valipour; Abdelkader T. Ahmed; Alper Baba; Esra B. Güngör; Laila Mandi; Vasileios A. Tzanakakis; Nektarios N. Kourgialas; Nicholas Dercas (Land)
At the beginning of human history, surface water, especially from rivers and springs, was the most frequent water supply source. Groundwater was used in arid and semi-arid regions, e.g., eastern Crete (Greece). As the population increased, periodic water shortages occurred, which led to the development of sophisticated hydraulic structures for water transfer and for the collection and storage of rainwater, as seen, for example, in Early Minoan times (ca 3200–2100 BC). Water supply and urban planning had always been essentially related: the urban water supply systems that existed in Greece since the Bronze Age (ca 3200–1100 BC) were notably advanced, well organized, and operable. Water supply systems evolved considerably during the Classical and Hellenistic periods (ca 480–31 BC) and during the Roman period (ca 31 BC–480 AD). Also, early Indian society was an amazing vanguard of technology, planning, and vision, which significantly impacted India’s architectural and cultural heritage, thus laying the foundation for sustainable urban living and water resource management. In ancient Egypt, the main source of freshwater was the Nile River; Nile water was conveyed by open and closed canals to supply water to cities, temples, and fields. Underground stone-built aqueducts supplied Nile water to so-called Nile chambers in temples. The evolution of water supply and urban planning approaches from ancient simple systems to complex modern networks demonstrates the ingenuity and resilience of human communities. Many lessons can be learned from studying traditional water supply systems, which could be re-considered for today’s urban sustainable development. By digging into history, measures for overcoming modern problems can be found. Rainwater harvesting, establishing settlements in proximity of water sources to facilitate access to water, planning, and adequate drainage facilities were the characteristics of ancient civilizations since the ancient Egyptian, Minoan, Mohenjo-Daro, Mesopotamian, and Roman eras, which can still be adopted for sustainability. This paper presents significant lessons on water supply around the world from ancient times to the present. This diachronic survey attempts to provide hydro-technology governance for the present and future.